DIGITALISASI UMKM DENGAN MENGGUNAKAN PENDEKATAN TOE MODEL - Cahyadi, Luh Diah Citra Resmi; Pradnyani, Ni Luh Putu Sri Purnama (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022DO - 10.24843/EEB.2022.v11.i09.p10, 2022)
Digital transformation in MSMEs requires readiness in term s of technology, organization and the external environment of the business. Using the TOE Framework approach, this study aims to determine the readiness of MSME actors in digitizing. Applying multiple linear regression analysis techniques with a total of 119 respondents, this study found that technology through perceived relative advantage affects business readiness in making e-commerce, e-payment and e-finance. Perceived complexity also affects the readiness of business actors in making e-commerce. Organizations through the support of top management affect the readiness to use digital sales applications while communication affects the readiness of business actors to use digital payments and finance. The external environment through the support of internet provider companies and government support affects the readiness of business actors in making digital sales and payments.